The Not4 RING E3 Ligase: A Relevant Player in Cotranslational Quality Control. (21st January 2013) - Collart, Martine A.
Abstract : The Not4 RING E3 ligase is a subunit of the evolutionarily conserved Ccr4-Not complex. Originally identified in yeast by mutations that increase transcription, it was subsequently defined as an ubiquitin ligase. Substrates for this ligase were characterized in yeast and in metazoans. Interestingly, some substrates for this ligase are targeted for polyubiquitination and degradation, while others instead are stable monoubiquitinated proteins. The former are mostly involved in transcription, while the latter are a ribosomal protein and a ribosome-associated chaperone. Consistently, Not4 and all other subunits of the Ccr4-Not complex are present in translating ribosomes. An important function for Not4 in cotranslational quality control has emerged. In the absence of Not4, the total level of polysomes is reduced. In addition, translationally arrested polypeptides, aggregated proteins, and polyubiquitinated proteins accumulate. Its role in quality control is likely to be related on one hand to its importance for the functional assembly of the proteasome and on the other hand to its association with the RNA degradation machines. Not4 is in an ideal position to signal to degradation mRNAs whose translation has been aborted, and this defines Not4 as a key player in the quality control of newly synthesized proteins.